Three New Orchids from Southern India - Saldanha, J. Cecil (Indian Forester, 1974)
"Three new orchids Eulophia emllianae Saldanha, Oberonia josephi Saldanha and Phalaenopsis mysorensis Saldanha are described from South Inda".